Monitoring and Management of Tomato Leaf Miner, (Tuta absoluta, Meyrick) in Kavrepalanchowk, Nepal - Adhikari, Debraj; Subedi, R; Gautam, S; Pandit, D P; Sharma, D R (Journal of Agriculture and Environment, 2019)
Available with full text.